A feasibility study on the use of expert system in the cataloging of Filipiniana resources - Santos, Joven D. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This is about the feasibility of using an expert system in the cataloging of Filipiniana materials. A prototype expert system was developed and tested using 30 users as sample respondents.